Analysis of cross-reactivity between flaviviruses with sera of patients with Japanese encephalitis showed the importance of neutralization tests for the diagnosis of Japanese encephalitis. Issue 10 (October 2019) - Maeki, Takahiro; Tajima, Shigeru; Ikeda, Makiko; Kato, Fumihiro; Taniguchi, Satoshi; Nakayama, Eri; Takasaki, Tomohiko; Lim, Chang-Kweng; Saijo, Masayuki
Abstract: Japanese encephalitis (JE) is one of the most important viral encephalitis in Asia. JE is caused by the Japanese encephalitis virus (JEV), which belongs to the genus Flavivirus, family Flaviviridae . The diagnosis of JE is usually based on serological assays, and it has been reported that cross-reactivity between flaviviruses has complicated the interpretations of results from serological assays. Therefore, analysis of the cross-reactivity is an important subject for serological diagnosis of JE and other diseases caused by flaviviruses. In the present study, the cross-reactivity of the sera of patients with JE to other flaviviruses was analyzed using enzyme-linked immunosorbent assay (ELISA) and neutralization tests. Sixteen serum samples were collected from patients with JE and were tested for: i) IgM antibody against West Nile virus (WNV), dengue virus (DENV), zika virus (ZIKV), and tick-borne encephalitis virus (TBEV) using IgM-ELISA, ii) IgG antibody against DENV and TBEV using IgG-ELISA, and iii) neutralization tests with DENV 1–4, ZIKV, TBEV, and WNV. Out of the 16 samples tested using ELISA, 11 and 14 samples were positive for IgM and IgG, respectively, against at least one of the other flaviviruses. In neutralization tests, neutralizing potency against DENV, ZIKV, or TBEV was not detected in any samples. Although 13 samples showed neutralizing potency against WNV, their neutralizing antibody titers were equal to or less than one-eighth of those against JEV. These results show that neutralization tests are more specific than ELISA, indicating the importance of the neutralization tests in the diagnosis of JE.